Institutional challenges to intermodal transport and logistics governance in port regionalisation and hinterland integration - Monios, Jason (Transport and mobility series, 2014)
"This book provides an overview of intermodal transport and logistics including the policy background, emerging industry trends and academic approaches. Establishing the three key features of intermodal transport geography as intermodal terminals, inland logistics and hinterland corridors, Jason Monios takes an institutional approach to understanding the difficulties of successful intermodal transport and logistics. Key areas of investigation include the policy and planning background, the roles of public and private stakeholders and the identification of emerging strategy conflicts"--Publisher.